Loss of Tropomodulin4 in the zebrafish mutant träge causes cytoplasmic rod formation and muscle weakness reminiscent of nemaline myopathy - Joachim Berger; Hakan Tarakci; Silke Berger; Mei Li; Thomas E. Hall; Anders Arner; Peter D. Currie (Disease Models & Mechanisms, 2014)
Nemaline myopathy is an inherited muscle disease that is mainly diagnosed by the presence of nemaline rods in muscle biopsies. Of the nine genes associated with the disease, five encode components of striated muscle sarcomeres. In a genetic zebrafish screen, the mutant träge (trg) was isolated based on its reduction in muscle birefringence, indicating muscle damage. Myofibres in trg appeared disorganised and showed inhomogeneous cytoplasmic eosin staining alongside malformed nuclei. Linkage analysis of trg combined with sequencing identified a nonsense mutation in tropomodulin4 (tmod4), a regulator of thin filament length and stability. Accordingly, although actin monomers polymerize to form thin filaments in the skeletal muscle of tmod4trg mutants, thin filaments often appeared to be dispersed throughout myofibres. Organised myofibrils with the typical striation rarely assemble, leading to severe muscle weakness, impaired locomotion and early death. Myofibrils of tmod4trg mutants often featured thin filaments of various lengths, widened Z-disks, undefined H-zones and electron-dense aggregations of various shapes and sizes. Importantly, Gomori trichrome staining and the lattice pattern of the detected cytoplasmic rods, together with the reactivity of rods with phalloidin and an antibody against actinin, is reminiscent of nemaline rods found in nemaline myopathy, suggesting that misregulation of thin filament length causes cytoplasmic rod formation in tmod4trg mutants. Although Tropomodulin4 has not been associated with myopathy, the results presented here implicateTMOD4 as a novel candidate for unresolved nemaline myopathies and suggest that the tmod4trg mutant will be a valuable tool to study human muscle disorders.